Efficient and Direct Identification of Ditylenchus destructor and D. dipsaci in Soil and Plant Tissues Using a Species-Specific PCR Assay - Xu Han; Qing Chang; Youxian Xu; Pengjun Wang; Huixia Li; Yunqing Li; Yanshan Li; Wenkun Huang; Lingan Kong; Shiming Liu; Deliang Peng; Huan Peng (Horticulturae, 2024)
Ditylenchus destructor and D. dipsaci are important nematodes that have a significant economic impact on agronomic and horticultural plants worldwide. Microscopic observation alone may not distinguish between D. destructor and D. dipsaci. Accurate and rapid identification of these two species is essential for effective pest management. In the present study, a species-specific PCR assay was developed to detect and differentiate D. destructor and D. dipsaci based on the rDNA-ITS sequences. The primers developed in this study can specifically amplify fragments of DNA from D. destructor and D. dipsaci in the target population, without amplifying DNA from other non-target nematodes within the genus Ditylenchus. The sensitivity test revealed that this procedure has the ability to detect single second-stage juveniles (J2) of D. dipsaci at a dilution of 1/128 and D. destructor at a dilution of 1/64. Additionally, it can detect genomic DNA (gDNA) at concentrations of 10 pg/µL for D. dipsaci and 1 ng/µL for D. destructor. These results align with previously reported results obtained through RPA and LAMP methods. Furthermore, the primers developed in this study for D. destructor not only were able to amplify six different haplotypes of nematodes but also successfully detected it in infested plant roots and soil samples, thereby shortening the time and reducing the number of steps required for detection. Thus, this assay, which does not necessitate taxonomic or morphological expertise, significantly enhances the diagnosis of D. destructor and D. dipsaci in infested fields. This advancement aids in the early control of these nematodes.